2021
DOI: 10.1371/journal.pntd.0009647
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced attraction of sand fly vectors of Leishmania infantum to dogs infected with zoonotic visceral leishmaniasis

Abstract: Background The sand fly Phlebotomus perniciosus is the main vector of Leishmania infantum, etiological agent of zoonotic visceral leishmaniasis in the Western Mediterranean basin. Dogs are the main reservoir host of this disease. The main objective of this study was to determine, under both laboratory and field conditions, if dogs infected with L. infantum, were more attractive to female P. perniciosus than uninfected dogs. Methodology/Principal findings We carried out a series of host choice experiments and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
(74 reference statements)
1
10
0
Order By: Relevance
“…During the entomological investigation carried out during two consecutive years, 2009 and 2010, sandflies belonging to the subgenus Larroussius were predominantly P. perniciosus , P. longicuspis , and P. perfiliewi . These findings are concordant with previous studies performed in Northern Tunisia showing the predominance of these sandfly species [ 21 , 24 , 30 ]. The phenology of sandfly species performed from May to November 2010 showed two main peaks: a small one in June and a second larger one in September–October.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…During the entomological investigation carried out during two consecutive years, 2009 and 2010, sandflies belonging to the subgenus Larroussius were predominantly P. perniciosus , P. longicuspis , and P. perfiliewi . These findings are concordant with previous studies performed in Northern Tunisia showing the predominance of these sandfly species [ 21 , 24 , 30 ]. The phenology of sandfly species performed from May to November 2010 showed two main peaks: a small one in June and a second larger one in September–October.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies performed by our group showed that PUNV or closely related antigenic variants are able to infect humans, but at a low rate [ 47 ] compared with dogs [ 46 ]. The low sero-prevalence observed among humans compared with dogs could be explained by the zoophilic behavior of sandfly species of the subgenus Larroussius, mainly P. perniciosus [ 30 ]. More studies are needed to investigate the epidemiological impact of PUNV on humans and on dogs and the relationship with Leishmania infantum , an etiological agent of zoonotic visceral leishmaniasis [ 30 , 48 , 49 ], as both pathogens are transmitted by the same sandfly species belonging to the subgenus Larroussius [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on human malaria have supported this hypothesis, showing that Anopheles mosquitos are more attracted to infected people (Yan et al, 2021). Likewise, Chelbi et al (2021) observed that Leishmania-infected hosts are more attractive to sand flies. This phenomenon could be potentially explained by the increased emission of olfactory attractants from infected hosts (Yan et al, 2021).…”
Section: Evolutionary Consequences Of Vector Transmission For Pathogensmentioning
confidence: 71%
“…Likewise, Chelbi et al . ( 2021 ) observed that Leishmania -infected hosts are more attractive to sand flies. This phenomenon could be potentially explained by the increased emission of olfactory attractants from infected hosts (Yan et al ., 2021 ).…”
Section: Evolutionary Consequences Of Vector Transmission For Pathogensmentioning
confidence: 99%
“…Recent published data show that Leishmania -infected dogs were significantly more attractive to P. perniciosus than uninfected dogs under both laboratory and field conditions [ 22 ] . A similar behavior was detected when L longipalpis was tested [ 23 ].…”
mentioning
confidence: 99%